Kualitas Mikrobiologis Se’i Sapi yang di Curing Menggunakan Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) - Kristoforus Trifonius Missa; Oktovianus R. Nahak T.B.; Kristoforus W. Kia (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
The purpose of this study was to analyze the antibacterial activity of red dragon fruit peel extract against Escherichia coli and its application as a preserfative of beef. Data were processed by analysis of variance (ANOVA) and continued with Duncan test. Based on antagonistic tests using a diffusion method, red dragon fruit peel extract showed the ability to inhibit and even kill E. coli. Microbiological testing of beef shows that the use of red dragon fruit peel extract can inhibit the growth of pathogenic bacteria. This inhibition is caused by the presence of active compounds that act as antibacterial compounds in the skin of red dragon fruit thus suppressing the growth rate of pathogenic bacteria. Microbiological quality of cows with the addition of preservatives (nitrates) is still in accordance with SNI, but the number of bacteria in the addition of preservatives is more when compared to cows with the addition of concentrations of red dragon fruit peel extract which are fewer and still in accordance with SNI. Observation of the presence of E. coli bacteria in beef se'i both in control and treatment using preservatives and the concentration of red dragon fruit peel extract showed that there was no (negative) growth of E coli bacteria. The inhibition of the presence of E. coli bacteria is caused by the presence of red dragon fruit peel extract and bactericidal smoke content so that it can inhibit the growth of E. coli bacteria. It was concluded that the higher concentration of red dragon fruit peel extract (Hylocereus polyrhizus) will be better in the process of inhibition of the growth of Escherichia coli bacteria and potentially as a natural preservative that can be added to se'i products. The use of dragon fruit peel extract by 60% in se'i-making products as a curing agent can also reduce the rate of bacterial growth. The use of red dragon fruit peel extract by 60% in this test is also better when compared to control (-), control (+) and concentration of 50%.